Differential Effects of Human SP-A1 and SP-A2 on the BAL Proteome and Signaling Pathways in Response to Klebsiella pneumoniae and Ozone Exposure - Wang, Guirong; Umstead, Todd M.; Hu, Sanmei; Mikerov, Anatoly N.; Phelps, David S.; Floros, Joanna (Frontiers in Immunology, 2019)
Surfactant protein A (SP-A) plays critical roles in host defense, regulation of inflammation and surfactant metabolism in the lung. The human SP-A locus consists of two functional genes, SFTPA1 and SFTPA2 encoding surfactant proteins SP-A1 and SP-A2, respectively. Structural and functional differences exist between SP-A1 and SP-A2 in vitro and in vivo. Ozone is a major air pollutant with a negative impact on many biological processes. In this study we used humanized transgenic (hTG) SP-A1 and SP-A2 mice, and SP-A KO mice to study in vivo effects of SP-A1 and SP-A2 on the bronchoalveolar lavage (BAL) proteomic profile and associated signaling pathways in response to ozone or filtered air (FA) exposure and Klebsiella pneumoniae infection. The BAL samples were harvested 24 hrs after ozone (2 ppm for 3 hrs) or FA exposure and infection and analyzed by two-dimensional difference gel electrophoresis (2D-DIGE) and MALDI-ToF/ToF. We found: that 1) Ozone exposure, but not infection, is a major factor for increases in total BAL protein content. 2) A total of 36 proteins were identified, accounting for 89.62% of the BAL proteins resolved by the 2D-DIGE system. 3) The number of proteins in which levels were altered more than 25% following infection and FA exposure was: SP-A2 > SP-A1 > KO for male mice, and SP-A2 ≈ SP-A1 > KO for female mice. 4) The number of proteins with more than 25% increase/decrease after ozone exposure and infection was: SP-A2 > SP-A1 ≈ KO, with the majority being increases in male mice and decreases in female mice. 5) Eleven out of the 36 proteins, including annexin A5, glutathione S-transferase A4, SP-A1/SP-A2, and 14-3-3 zeta protein, exhibited significant differences among SP-A genotypes. Furthermore, Four signaling pathways, including acute phase response (APR) and Nrf2-mediated oxidative response were identified to be associated with SP-A genotype, sex, and ozone-induced oxidative stress in response to infection. We concluded that human SP-A2 and SP-A1 exhibit differential genotype-and sex-dependent innate immune responses to microbial pathogens and/or ozone-induced oxidative stress by modulating proteomic patterns and signaling pathways in the lung.